Nutritive value of cattle manure vermicast and its effect on in vitro ruminal gas production - Nasiru, Aminu; Alimon, Abdul Razak; Ismail, Norli; Ibrahim, Mahamad Hakimi (SpringerOpen, 2014)
Introduction The use of non-conventional feedstuffs is gaining recognition especially in developing countries. Ensiled cattle manure with other feedstuffs has been used in ruminant feeding. Vermicomposting, a tool for manure management can be employed as a means for manure treatment with the aim of enhancing nutritive value of forage. The objectives of the study were to determine the nutritive value of cattle manure vermicast (CMV) and to observe gas production in vitro due to CMV inclusion on rice straw at different proportions. Results Vermicomposting of cattle manure at 2, 4 and 6 weeks linearly increased (P < 0.05) significantly crude protein and ash, while it linearly decreased (P < 0.05) significantly organic matter, neutral detergent fibre (NDF) and acid detergent fibre. The result showed that, gas production decline with an increased in CMV content (P < 0.05). CMV addition to rice straw had no significant (P > 0.05) effect on rumen pH and microbial crude protein production in vitro. CMV inclusion reduced dry matter degradability and increased partitioning factor at 48 h. 5 % inclusion level of CMV gave the highest results while 30 % CMV had the least results. Conclusion Vermicomposting of cattle manure increased its nutritive value, with increase in crude protein content and decrease in NDF and ADF. Results of in vitro gas production and rumen fermentation profiles from this study indicated that inclusion of CMV reduced gas production and DMD; however, it increased PF48, with no significant changes in MCP. Vermicomposting has the potential of being used as another tool for forage treatment and addition of CMV could be expected to reduce ruminant gas production, increase ME and microbial protein synthesis.